2019
DOI: 10.3390/ijerph16040675
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Environmental Efficiency and Technology Gap of PM2.5 in China’s Ten City Groups: An Empirical Analysis Using the EBM Meta-Frontier Model

Abstract: Since air pollution is an important factor hindering China’s economic development, China has passed a series of bills to control air pollution. However, we still lack an understanding of the status of environmental efficiency in regard to air pollution, especially PM2.5 (diameter of fine particulate matter less than 2.5 μm) pollution. Using panel data on ten major Chinese city groups from 2004 to 2016, we first estimate the environmental efficiency of PM2.5 by epsilon-based measure (EBM) meta-frontier model. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…4. China has not achieved coordinated development between the environment and economic growth in the past decade (Cheng et al, 2019). This is similar to our conclusion.…”
Section: Discussion and Limitations Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…4. China has not achieved coordinated development between the environment and economic growth in the past decade (Cheng et al, 2019). This is similar to our conclusion.…”
Section: Discussion and Limitations Discussionsupporting
confidence: 88%
“…Their results show that high-income cities have higher average efficiencies than uppermiddle income cities. Cheng et al (2019) estimate the environmental efficiency of PM2.5 by the epsilon-based measure (EBM) meta-frontier model. Their findings offer large differences in PM2.5 environmental efficiency between cities and city groups.…”
Section: Air Quality Efficiency Evaluation Based On Data Envelopment Analysis Methodsmentioning
confidence: 99%
“…Data envelopment analysis has been used for a long time and has proven to be a successful methodology for evaluating the performance of a group of homogeneous decision-making units (DMUs) based on their multiple inputs and outputs. The implementation of DEA in evaluating renewable resources performance, renewable energy studies, position in sustainability, energy efficiency, as well as other disputes related to energy and environment have been studied [5][6][7][8]. Additionally, as cited from different research, EBM is being applied to analyze production and efficiency; to compare efficiency values; to reduce emissions and for efficiency of PV industry; to see differences in carbon emissions, efficiency, and technology gap; to evaluate the process in procurement; to analyze traditional energy, to operate performance; and to measure the total factor energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies pay more attention to explicating what contributes to atmospheric pollution of the YRB considering meteorological and human factors [26].Statistical analysis methods are frequently applied to describe the pollution sources, especially though time series analysis and spatial analysis [27,28]. Mathematical research has revealed single factors, such as spatiotemporal variation, meteorological factors, pollution sources, socioeconomic factors, etc.[29] Regarding the environmental incidents, researchers focus more on environmental quality evaluation systems in the metropolis of the YRB [30,31]. The analysis of deep causes (not only from objective data) and the interaction of factors are critical, but often-overlooked, components of air pollution, which may contribute to biased conclusions.…”
mentioning
confidence: 99%
“…[29] Regarding the environmental incidents, researchers focus more on environmental quality evaluation systems in the metropolis of the YRB [30,31]. The analysis of deep causes (not only from objective data) and the interaction of factors are critical, but often-overlooked, components of air pollution, which may contribute to biased conclusions.…”
mentioning
confidence: 99%